Elastography Applications in Clinical Medicine - Stoian, Dana; Popescu, Alina (IntechOpen, 2022)
Elastography is a recent application of conventional ultrasound evaluation with recognized benefits in the field of malignancy risk assessment and disease evolution prediction. This book examines the use of this technique in non-alcoholic fatty liver disease (NAFLD), alcohol-induced liver disease, liver fibrosis, chronic hepatitis, portal hypertension, and hepatic tumors. It also discusses the use of elastography in the pediatric population for thyroid disease and hepatic, or musculoskeletal diseases. Nonabdominal elastography applications are also presented, such as in breast pathology, thyroid diffuse and nodular disease, renal chronic disease, parathyroid hyperplasia and chronic musculoskeletal impairment.